Cancer Mortality among Persons with Human Immunodeficiency Virus Infection in New York City, 2001–2015. (4th October 2017) - Ramaswamy, Chitra; Westheimer, Emily; Braunstein, Sarah
Abstract: Background: With the prolonged life-span of persons with HIV (PWH) due to anti-retroviral therapy, their cancer burden has increased. Cancer continues to be a leading cause of death among PWH. Studying cancer mortality can inform and guide the development of cancer screening and prevention strategies for PWH. Methods: We analyzed data for all persons > = 13 years who were diagnosed with HIV from 2001 to 2015 and reported to the New York City (NYC) HIV surveillance registry (HSR). Using the HSR and the underlying cause of death obtained from the NYC vital statistics registry and the National Death Index, we examined age-specific and age-standardized mortality rates from cancer and compared time trends of deaths due to HIV-related8 cancer to deaths from non-HIV-related cancers. Results: There were 34, 190 deaths reported among 154, 688 PWH of whom nearly half ( n = 16, 804; 49.1%) died due to HIV (excluding HIV-related cancers). Among all deaths, HIV was the leading cause, followed by cancer (both HIV and non-HIV-related) ( n = 5, 271; 15.4%) and cardiovascular disease ( n = 3, 724, 10.9%). The top three causes of non-HIV-related cancer deaths were lung cancer ( n = 1, 040; 19.7%), liver cancer ( n = 552; 10.5%), and colorectal cancer ( n = 315; 5.6%). Although the mortality rate among PWH decreased over time (24.4 to 13.9 per 1, 000 person-years from 2001 to 2015), the proportion of deaths attributable to all cancers increased (10.6% in 2001 to 19.9% in 2015, p < .0001). This increase was driven by non-HIV-related cancers (6.1% of all deaths in 2001 to 15.8% in 2015, p < .0001). The mean age increased from 2001 to 2015 among the dead (46 to 56 years) and among the censored (35 to 49 years). After controlling for demographic factors, transmission risk, and last CD4 count, the hazard ratio for cancer deaths was higher among people who inject drugs (HR = 1.5; 95% CI = 1.4–1.7) and those with last CD4 count < 200 (HR = 9.3; 95% CI = 8.3–10.5). Conclusion: Although mortality rates are decreasing in PWH, deaths due to non-HIV-related cancers are increasing. The upward trend in the mean age suggests that aging may be contributing to this increase. Routine screening for liver and colon cancers along with smoking cessation may reduce lung, liver and colon cancer deaths. Disclosures: All authors: No reported disclosures.